BIOLOGIA E CULTURA: SIGNIFICAÇÕES PARTILHADAS NA LITERATURA DE MONTEIRO LOBATO1 - Carvalho, Fabiana Aparecida De [UNESP] (Faculdade de Educação da Universidade Federal de Minas Gerais, 2007)
The texture of this work accumulates of stocks biology as cultural production and argues its in tickets for the Lobato's literature, particularly in the work The key of size. Biological traces (situated according Derrida) as size, evolution, and biological world flow and mix with other meanings and relationships and senses that occur among spaces - differences - of the multiple knowledge. One argues the relations of the differentiations that are established between Literature and Biology and the intensity of the narratives that bring traces of beliefs, values and political interests in the scientific speech and that are brought into the literature in hybrid direction.

A tessitura deste trabalho abarca a biologia como produção cultural e discute seus significados em passagens pela literatura de Monteiro Lobato, particularmente na obra A Chave do Tamanho. Traços biológicos (situados segundo Derrida) como tamanho, evolução, mundo biológico se hidridizam e se mesclam a outros significados e apontam relações e significações que se dão entre espaços - diferenças - dos múltiplos conhecimentos. Discutem-se as relações de diferenças que se estabelecem entre a Literatura e Biologia - hibridizando-as - e a intensidade de narrativas que trazem traços de crenças, valores, interesses políticos no discurso científico e que são arrastados para a Literatura.
BIOLOGY AND CULTURE: MEANINGS SHAREDS IN MONTEIRO LOBATO'S LITERATURE
Keywords: biology; cultural production; Monteiro Lobato's literature and literature.; biologia; produção cultural; literatura e Monteiro Lobato.